The development of ion regulation in larval rainbow trout, Oncorhynchus mykiss - Misiaszek, Christina (My University, 1996)
The development of Na+ and Ca++ transport, ammonia excretion, and respiration in larval rainbow trout were studied over the period of yolk sac absorption and shortly after the onset of exogenous feeding. The gills and the yolk sac epithelium of larvae were examined for any indication of the presence of mitochondria-rich cells and/ or Na-K-ATPase activity.
Whole body Na+ content of the larvae increased throughout yolk sac absorption and after the onset of exogenous feeding. During this period there was an increase in Na+ influx, efflux, transporter capacity Umax> and transporter affinity (Km). Jmax increased 4.6 times during yolk sac absorption, and increased another 2.8 times 248 degree·days after the onset of exogenous feeding. Km decreased over the first 168 degree·days and stayed constant for the remainder of the experimental period. The gills were the primary site of Na+ efflux. Na+ accumulation from the water began the first day post hatch.
Ca++ transport capacity increased throughout yolk sac absorption, but then decreased after the onset of exogenous feeding. Jmaxca++ exhibited a 15.5 fold increase over 257 degree·days, which then decreased to 30% of that value after exogenous feeding commenced. There was a 162 fold increase in Ca++ Km over yolk sac absorption, which then decreased 15.6 times after the onset of exogenous feeding. Whole body Ca++ began to increase approximately 200 degree·days post-hatch and exhibited a large increase after the onset of exogenous feeding. It is possible that during yolk sac absorption the larvae does not begin to accumulate Ca++ from the external environment until its internal reserves are depleted, and with the onset of feeding the larvae then obtains its Ca++ from its diet.
Ammonia excretion in larval trout increased 3.6 times over yolk sac absorption, and increased another 2.8 times after exogenous feeding commenced. There was no evidence of a link between Na+ uptake and NJ-:4+ excretion in larval fish as NJ-:4+ excretion was not stimulated in response to increasing external Na+ concentrations. Measurements of the ammonium concentration at different surfaces of the larvae revealed a larger ammonium concentration next to the gills than next to the yolk sac and skin. This may indicate that the gills are the primary site for ammonia excretion in the larval fish.
Initially, branchial and cutaneous surfaces contributes to respiration, but as the gills grow and develop and the yolk sac decreases in size and the skin thickens, the contribution of the gills to this function increases.
The gills of first day hatchlings are comprised of gill arches and filaments. Lamellae do not begin to develop until a few days after hatching. The gill filaments contain mitochondria-rich cells and have Na-K-ATPase activity as determined through binding of the fluorescent dye anthroylouabain. The yolk sac epithelium contained cells with concentrated regions of mitochondria, but significant Na-K-ATPase activity was not detected when compared to branchial staining.
Keywords: ion regulation; rainbow trout; Oncorhynchus mykiss; larval trout